Increasing Tourist Attraction through Aesthetic Development of Kayu Angin Beach, Samaturu Sub-district - Arjun; Hamira, Sunatul Mutahahir; Febriyanti, Annisa; Ardianto, Mila Adipati; Ferdi, Ferdi; Hasanuddin, Hasanuddin; Mujahida, Ummul; Syaiful, Muhammad; Sapriyadi, Sapriyadi (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
Indonesia has many tourist attractions that have an attraction, especially marine tourism, one of the marine tourism that can be visited is Kayu Angin beach. Based on the results of a survey conducted at Kayu Angin beach, it was found that some facilities were outdated and the colors had begun to fade, thus reducing their beauty. At Kayu Angin beach, it is very difficult to find trash bins, and the condition of the coast is very dirty with a lot of garbage. This service activity was carried out to restore beach maintenance and cleanliness and improve beach aesthetics. The method used is participatory observation. The series of activities: 1. Coordinating with the beach manager, 2. Conducting a location survey, and 3. Repainting, providing trash bins, and cleaning the coastline. After this activity the beach atmosphere became more lively and attractive to visitors. Thus, painting, providing trash bins and cleaning the coastline are effective strategies in improving aesthetics and maintaining beach cleanliness. This activity can be implemented continuously by the surrounding community so that the beach is maintained and maintained cleanliness so as to attract tourists to visit.